Managing Salt Ratios in Saline Water Irrigated Cotton-Wheat Cropping System by Farm Yard Manure and Sewage Sludge: Managing salt ratios in saline irrigation in cotton wheat cropping system - Singh, Charan; Prakash, Ram; Raj, Dev; Kumari, Gayatri; Sharma, Mohit (Journal of Soil Salinity and Water Quality, 2025)
A field experiment was conducted during 2021–22 at Hisar using two irrigation treatments, viz. canal water (I1: 0.30 dS m-1) and saline water (I2: 8 dS m-1) and eight fertilizer/manure treatments, viz. T1: control, T2: farm yard manure (FYM) 10 Mg ha-1, T3: sewage sludge (SS) 5 Mg ha-1, T4: 100% recommended dose of fertilizer (RDF), T5: 75% RDF+10 Mg ha-1 FYM+ST-3 (Azotobacter), T6: 75% RDF+5 Mg ha-1 SS+ST-3, T7: 100% recommended dose of nitrogen (RDN)+75% P&K+10 Mg ha-1 FYM+ST-3, T8: 100% RDN+75% P & K+5 Mg ha-1 SS+ST-3. The aim of this investigation was to evaluate the impact of integrated nutrient management and saline water irrigation on salt ratios in cotton-wheat crop rotation. The FYM and SS were applied in the Kharif season only. Na+/K+ and Cl-/SO42- ratio were significantly increased with increased irrigation water salinity in cotton and wheat crops. However, RDF, organic manures and integrated nutrient management treatments resulted in lower Na+/K+ and Cl-/SO42- ratio in cotton and wheat as compared with control. The Na+/K+ ratio was reported lowest with T7 in seed and stalk of cotton, while it was lowest with T4 in wheat grain and straw as compared to control. Similarly, the Cl-/SO42- ratio was reported lowest with T7 in cotton seed, stalk and wheat straw compared to control. It may be concluded that combined application of FYM, SS and inorganic fertilizers increases the potential of agricultural crops to withstand salt stress by decreasing Na+ and Cl- besides increasing the K+ and SO42- in the plants.